Constitutional right to a safe and healthy environment - Kashyntseva , Oksana; Safonova , Maria (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
This article provides a comprehensive and interdisciplinary analysis of the constitutional right to a safe and healthy environment within the framework of contemporary global and national challenges. It begins by outlining the historical evolution of environmental rights, tracing their emergence from early philosophical and legal thought to their inclusion in international human rights instruments and national constitutions. The study highlights the growing recognition of environmental degradation as a human rights issue, especially through the case law of the European Court of Human Rights. Special attention is given to the Ukrainian context, where the right to a safe environment is enshrined in Article 50 of the Constitution. The article explores how this right has been implemented and protected, and how it intersects with international legal obligations and standards. In light of the full-scale Russian invasion of Ukraine in 2022, the paper addresses the environmental consequences of war, the destruction of ecosystems, and the weakening of environmental governance. The conflict has exposed the vulnerabilities of environmental protection mechanisms during wartime and emphasized the importance of including ecological security in national security frameworks.The paper also discusses the role of public participation, access to environmental information, and judicial remedies, drawing on the principles of the Aarhus Convention. It calls for a rights-based and sustainable approach to environmental governance and urges the integration of environmental rights into broader development, security, and resilience policies. The author argues that the realization of constitutional environmental rights is essential for safeguarding human dignity, intergenerational justice, and the sustainability of democratic societies.